MOCERA TASI RITUAL AMONG THE WOTU COMMUNITY IN EAST LUWU (The Maslahat Perspective) - Zulhas'ari Mustafa (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
This article deals with the explanation of local celebration called mocera tasi performed by the ethnic Wotu community in East Luwu District. The focus of the research is closely related to the values understood by the Wotu ethnic community, in relation to the ritual of mocera tasi. Such Values, according to Community understanding, were derived from the cultural practices within the community. The ritual, in addition, was carried out by the Wotu community in order to legitimize the leadership of the Macowa Bawalipu  as Wotu traditional leaders, to expressing gratitude to Allah SWT, and to rejecting reinforcements. The mocera tasi rituals as a ritual for ratifying traditional leaders are classified as adat rituals. Mocera tasi, in addition, as an expression of gratitude and refusal of reinforcements is also classified as folk ritual. The benefit to be achieved in the ritual of mocera tasi is linked to the maintenance of the benefit of Nasab  (family blood) and wealth. The level of the benefit of the ritual of mocera tasi is at the level of ḥājiyyat.